Marriage, work, and migration: The role of infrastructure development and gender norms - Amrit Amirapu; Mohammad Niaz Asadullah; Zaki Wahhaj (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Traditional gender norms can restrict independent migration by women, preventing them from taking advantage of economic opportunities in urban non-agricultural industries. However, women may be able to circumvent such restrictions by using marriage to engage in long-distance migration-if they are wealthy enough to match with the desirable migrating grooms. Guided by a model in which women make marriage and migration decisions jointly, we hypothesize that marriage and labour markets will be inextricably linked by the possibility of marital migration. We use the construction of a major bridge in Bangladesh-which dramatically reduced travel time between the economically deprived north-western region and the industrial belt around Dhaka-as a source of plausibly exogenous variation in migration costs. In accordance with our model's predictions, we find that the bridge construction induced marriage-related migration (not economic migration) among rural women, but only for those women coming from families above a poverty threshold.
Keywords: J12; J16; O18; R23; 330; migration; marriage markets; female labour force participation; gender norms